Analisis Perbandingan Kinerja Keuangan Pemerintah Daerah Kota/Kabupaten Di Indonesia Sebelum Dan Setelah Pemekaran - Mengkuningtyas, Yeni; Adib, Noval (Jurnal Ilmiah Mahasiswa FEB, 2015)
This research aims to explore whether there are financial performance differences of local government  before  and  after  region  expansion.  The  financial  performance  of  local government   is   measured   by   financial   ratio   includes   financial   independence   ratio, effectiveness of local revenue ratio, efficiency ratio, accordance of capital expenditure ratio and  growth  of  local  revenue  ratio.  This  research  population  are  districts  or  cities  in Indonesia that expanded during 2008. The sample used in this research are 17 regions with purposive sampling methods. The data used in this research is secondary data from The Audit Board of the Republic of Indonesia (BPK RI). The data analysis technique used in this research are financial ratio and t-test (paired sample test). The t-test result shows that there is no significant value of financial independence ratio, effectiveness of local revenue ratio, efficiency ratio, accordance of capital expenditure ratio and growth of local revenue ratio. It can be concluded that there is no difference about the financial performance of local governments before and after region expansion in financial independence, effectiveness of local revenue, efficiency, accordance of capital expenditure and the growth of local revenue.     Keywords:   financial    performance,    independence,    effectiveness,    efficiency,    capital expenditure, growth, region expansion, local revenue